External influences on the development and professionalisation of accounting in Malaysia, 1957-1969 - Azham Md. Mi; Lee Teck Heang; Brian West (Indonesian Management and Accounting Research, 2011)
The accounting history literature identifies a tendency for accounting in developing countries to be dominated by the style of accounting institutions and practices of western developed nations - particularly the USA and UK.This "importation" hypothesis is investigated and refined through a case study examination of the history of accounting in Malaysia during the formative years of 1957 to 1969. This era commences with the Malay States gaining independence from Britain and closes with the race riots which marked a turning point in the nation's history. The establishment of the Malaysian Association of Certified Public Accountants (MACPA) in 1958 and the passing of the Companies Act of 1965 and the Accountants Act of 1967 are identified as key events which perpetuated British colonial influence within the new nation. These circumstances add credence to the "importation" hypothesis and support a depiction of accounting and its institutional apparatus as regularising forces with a capacity to transcend political and social change within a nation state.Keywords: accounting profession, professionalisation, Malaysia, colonialism